2023
DOI: 10.5194/egusphere-2023-683
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Anthropogenic activities significantly increase annual greenhouse gas (GHG) fluxes from temperate headwater streams in Germany

Abstract: Abstract. Anthropogenic activities increase the contributions of inland waters to global greenhouse gas (GHG; CO2, CH4, and N2O) budgets, yet the mechanisms driving these increases are still not well constrained. In this study, we quantified year-long GHG concentrations and fluxes, as well as water physico-chemical variables from 23 streams, 3 ditches, and 2 wastewater inflow sites across five headwater catchments in Germany contrasted by land use. Using mixed-effects models, we determined the overall impact o… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 35 publications
1
5
0
Order By: Relevance
“…These trends also reflect findings in terrestrial ecosystems, which have found agricultural soils to be hot spots of GHGs (e.g., Raich and Tufekciogul, 2000;Wangari et al, 2022). The above findings suggest that the annual oversaturation of GHGs within agricultural streams, as found in several other studies (e.g., Borges et al, 2018;Herreid et al, 2021;Mwanake et al, 2022Mwanake et al, , 2023, could be supported either by younger precipitation interflows through oversaturated soils or older groundwater nutrients.…”
Section: Agricultural E Ects On Mean Annual Water-physico-chemical Va...supporting
confidence: 85%
See 4 more Smart Citations
“…These trends also reflect findings in terrestrial ecosystems, which have found agricultural soils to be hot spots of GHGs (e.g., Raich and Tufekciogul, 2000;Wangari et al, 2022). The above findings suggest that the annual oversaturation of GHGs within agricultural streams, as found in several other studies (e.g., Borges et al, 2018;Herreid et al, 2021;Mwanake et al, 2022Mwanake et al, , 2023, could be supported either by younger precipitation interflows through oversaturated soils or older groundwater nutrients.…”
Section: Agricultural E Ects On Mean Annual Water-physico-chemical Va...supporting
confidence: 85%
“…While GHG dynamics of headwater catchments in this study were previously discussed by Mwanake et al (2023), the results of this study have contributed to a better conceptualization of catchment-scale land use effects linked to hydrological processes. We found notable differences in mean annual water physicochemical properties and GHG saturations among streams of catchments differing in agricultural areas and MRTs.…”
Section: Agricultural E Ects On Mean Annual Water-physico-chemical Va...mentioning
confidence: 56%
See 3 more Smart Citations